Effects of active acromegaly on bone mRNA and microRNA expression patterns. Issue 4 (April 2018) - Belaya, Zhanna; Grebennikova, Tatiana; Melnichenko, Galina; Nikitin, Alexey; Solodovnikov, Alexander; Brovkina, Olga; Grigoriev, Andrey; Rozhinskaya, Liudmila; Lutsenko, Alexander; Dedov, Ivan
Abstract : Objective: To evaluate the response of bone to chronic long-term growth hormone (GH) and insulin-like growth factor-1 (IGF1) excess by measuring the expression of selected mRNA and microRNA (miR) in bone tissue samples of patients with active acromegaly. Design: Case–control study. Methods: Bone tissue samples were obtained during transsphenoidal adenomectomy from the sphenoid bone (sella turcica) from 14 patients with clinically and biochemically confirmed acromegaly and 10 patients with clinically non-functioning pituitary adenoma (NFPA) matched by sex and age. Expression of genes involved in the regulation of bone remodeling was studied using quantitative polymerase chain reaction (qPCR). Results: Of the genes involved in osteoblast and osteoclast activity, only alkaline phosphatase (ALP) mRNA was 50% downregulated in patients with acromegaly. GH excess caused increased expression of the Wnt signaling antagonists ( DKK1) and agonists ( WNT10B) and changes in the levels of miR involved in mesenchymal stem cell commitment to chondrocytes (miR-199a-5p) or adipocytes (miR-27-5p, miR-125b-5p, miR-34a-5p, miR-188-3p) P < 0.05; q < 0.1. Relevant compensatory mechanisms were found through the changes in miR involved in osteoblastogenesis (miR-210-5p, miR-135a-5p, miR-211, miR-23a-3p, miR-204-5p), but the expression of TWIST1 was 50% downregulated and RUNX2 was unchanged. Conclusions: Acromegaly had minimal effects on tested mRNAs specific to osteoblast or osteoclast function except for downregulated ALP expression. The expressions of miR known to be involved in mesenchymal stem cell commitment and downregulated TWIST1 expression suggest acromegaly has a negative effect on osteoblastogenesis.